STATE FINANCIAL LOSSES PREVENTION POLICY DUE TO CORRUPTION IN GOODS AND SERVICE PROCUREMENT DURING THE PANDEMIC (Study of Decision Number 24/Pid.Sus-TPK/2024/PN Mdn and Decision Number 11/Pid.Sus-TPK/2023/PN Amb) - Namira Harahap; M. Ekaputra; Vita Cita Emia Tarigan (CV Rewang Rencang, 2024)
The COVID-19 pandemic is very risky and requires quick action and policy-making for the safety of all. For this reason, the government has taken a policy related to using specific budget allocations by facilitating the procurement process of goods and services to prevent and handle COVID-19. Still, in the process, many acts have occurred that are detrimental to state finances. The method used in this thesis is the normative legal research method, which refers to legal norms with data sources obtained by examining library materials to obtain secondary data in the form of primary, secondary, and tertiary materials. The study results found that in the two decisions studied, the judges had carefully considered the legal facts in the trial but still had different interpretations regarding the element of